If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w + -10 = -64 Reorder the terms: -10 + w = -64 Solving -10 + w = -64 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + w = -64 + 10 Combine like terms: -10 + 10 = 0 0 + w = -64 + 10 w = -64 + 10 Combine like terms: -64 + 10 = -54 w = -54 Simplifying w = -54
| -2m-7(4+3m)=28+5m | | 7a+26=20a | | 7*(2+n)=(7*2)+(7*1) | | x/5-8=3/10 | | 6t-7=29 | | 7(1+8x)-7x=7+4x | | 8n-4n+8n= | | X+4-3x=1+X | | 2.9=4.7-0.9x | | -2(2n-2)=13-n | | 4k-6=7-6k | | 7=0.2(x+15) | | 3x-5+2x=10+4x-3 | | 7(x^2-7x-30)=0 | | -3+49=-31 | | 3xy-5xy+21y= | | -3(2x-3)=-6x-9 | | 3(x+2)=-45 | | 50=37+m | | 1+7x=2x-4 | | n+n+0.6=n+0.1+2n | | 200-2x-2x-2=0 | | 5(3k+6)=7k+38 | | 8=x-5x+8 | | 6x+x=-6(x+1)-2(x-3) | | 65*n=0 | | 12x+x=2x+2 | | -5x+9=-51 | | 5t-9=(-3)t+7 | | 5(x^2-2x-48)=0 | | 0.32+0.23=0.40+6 | | 7*x+6=10*x |